Model-Implementation Fidelity in Cyber Physical System Design - Molnos, Anca; Fabre, Christian (Springer International Publishing : Imprint: Springer, 2017)
This book puts in focus various techniques for checking modeling fidelity of Cyber Physical Systems (CPS), with respect to the physical world they represent. The authors' present modeling and analysis techniques representing different communities, from very different angles, discuss their possible interactions, and discuss the commonalities and differences between their practices. Coverage includes model driven development, resource-driven development, statistical analysis, proofs of simulator implementation, compiler construction, power/temperature modeling of digital devices, high-level performance analysis, and code/device certification. Several industrial contexts are covered, including modeling of computing and communication, proof architectures models and statistical based validation techniques. Addresses CPS design problems such as cross-application interference, parsimonious modeling, and trustful code production Describes solutions, suchas simulation for extra-functional properties, extension of coding techniques, model-driven development, resource driven modeling, and quantitative and qualitative verification, based on statistics and formal proofs Applies techniques to several CPS design challenges, such as mixed criticality, communication protocols, and computing platform simulation.